2010
DOI: 10.1038/jhg.2010.92
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide pathway analysis implicates intracellular transmembrane protein transport in Alzheimer disease

Abstract: We developed and implemented software for the analysis of genome-wide association studies in the context of biological pathway enrichment and have here applied our algorithm to the study of Alzheimer disease (AD). Using genome-wide association data in a large French population, we observed a highly significant enrichment of genes involved in intracellular protein transmembrane transport, including several mitochondrial proteins and nucleoporins. An intriguing aspect of these findings is the implication that TO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 17 publications
3
46
1
Order By: Relevance
“…Previous Results from Pathway Analysis of AD GWAS Prior to this study, six pathway analyses of AD GWAS have been reported with five studies using the KEGG database [4][5][6][7][8][9]. We compared our findings with the previous pathway analyses of AD GWAS.…”
Section: Two Ad Brain Expression Gwas Datasetsmentioning
confidence: 76%
See 2 more Smart Citations
“…Previous Results from Pathway Analysis of AD GWAS Prior to this study, six pathway analyses of AD GWAS have been reported with five studies using the KEGG database [4][5][6][7][8][9]. We compared our findings with the previous pathway analyses of AD GWAS.…”
Section: Two Ad Brain Expression Gwas Datasetsmentioning
confidence: 76%
“…We compared our findings with the previous pathway analyses of AD GWAS. All of the pathway analysis results were publicly available from the original studies [4][5][6][7][8][9].…”
Section: Two Ad Brain Expression Gwas Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial dysfunction has been associated with several pathological processes in AD, such as brain hypometabolism, synaptic pathology, accumulation of APP, and Aβ influx to the cell [14][15][16]. Damaged mitochondria exert a specific influence on the AD pathophysiology through interplay with Aβ and its precursor, AβPP.…”
Section: Tomm40mentioning
confidence: 99%
“…Both the apolipoprotein E (APOE) gene and the TOMM40-APOE locus, tagged by rs2075650 in the translocase of outer mitochondrial membrane 40 (TOMM40) gene (see Supplementary Information), have been implicated (Hong et al, 2010;Li et al, 2008;Schiepers et al, 2011). Investigations of depression have also indicated that the APOE e4 risk allele influences both the onset and risk for late-life depression (Butters et al, 2003;Yen et al, 2007) and has been associated with gray matter reductions (Cherbuin et al, 2007), reduced white matter integrity (Heise et al, 2011) and cognitive impairment (Greenwood et al, 2000) in healthy adults, further suggesting that genetic mechanisms associated with dementia may contribute to the development of mood disorder.…”
Section: Introductionmentioning
confidence: 99%